Pediatric Massage as an Adjunctive Sensorimotor Strategy for Early Language Development in Toddlers with Speech Delay: A Structured Review - Farohatul Fitriyah; Reny Retnaningsih (Health and Technology Journal (HTechJ), 2026)
Speech delay in early childhood is a developmental problem that can affect communication skills, social interaction, and a child's future readiness. Various stimulation approaches have been developed to support language development, one of which is through non-pharmacological intervention in the form of massage therapy. This study aims to examine the effectiveness of massage therapy in stimulating language development in children with speech delay aged 2–3 years through a literature review method. Articles were searched using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) technique through the Google Scholar database with inclusion criteria of relevant research articles, full text, and involving early childhood subjects. The search and selection resulted in four articles that were analyzed in depth. The findings showed that massage therapy, including baby massage and oromotor massage, had a positive effect on sensory stimulation and children's communication readiness. The biological mechanisms underlying this intervention are related to sensorimotor stimulation, which can increase nerve activity, nervous system regulation, and the quality of vocal interaction between children and caregivers, thereby supporting the language acquisition process. Based on the results of the review, massage therapy has the potential to be an effective, safe, and easy-to-apply supportive intervention in stimulating language development in children aged 2–3 years